Bank governance contracts : establishing goals and accountability in bank restructuring - Roulier, Richard P. (Washington, D.C. : World Bank, 1995)
his report reviews the recent economic and political history of the Middle East and North Africa and discusses ways in which the region may capitalize on its natural, financial, and human resources to become a key player in an integrating global economy.
vi, 31p.
enc. 16/11/18, ijb 11/03/2019
Loan.
Keywords: Banking law; Bank management; Banks and banking; Banking law